Strategic Partnerships and Regional Security Architectures under Modi Regime (2014-2019) - Pooja Bhatt (ASIAN Journal of International Peace & Security (AJIPS), 2021)
How has Indian Prime Minister Modi’s domestic policies of Act East and Neighbourhood First Policy fared in consonance with his foreign policy objectives in the Indian Ocean Region and Indo-Pacific at the end of his first tenure? To answer this question, this paper presents empirical research that reviews the role and scope of the maritime component in India’s policy approach from 2014 till 2019 under Modi government towards regional peace and security. A reading of maritime trends informs the research that New Delhi has been taking a two-pronged, parallel approach to achieve its goals: India is establishing strategic partnerships at the bilateral level with countries through military exercises and defence-related trade. Simultaneously, at the multilateral, regional level New Delhi has shown an increasing interest in developing regional security architectures for engagement with like-minded countries having common regional interests and objectives. The research concludes that even though bilateral engagements are moving to delivering its aims of fostering cooperation, it is under the larger ambit of multilateralism that India needs to develop normative and operational maritime security frameworks /arrangements in the coming years.